Self-assembly and morphological control of three-dimensional macroporous architectures built of two-dimensional materials. (June 2017) - Kim, Ji-Eun; Oh, Jung-Hwan; Kotal, Moumita; Koratkar, Nikhil; Oh, Il-Kwon
Graphical abstract: Highlights: General approaches for self-assembled 3D porous hierarchical architectures from diverse 2D materials are presented. Synthesis methods and parameters for systems of both bulk gelation and interface mediated assembly are discussed. The demand for future applications of 2D-materials-based tailored 3D macroporous architectures is briefly illuminated. Abstract: The three-dimensional (3D) macroscopic assembly of tailored porous architectures built of graphene derivatives or other two-dimensional (2D) materials has attracted great attention in both academia and industry. The reason being that such 3D assemblies with controlled morphology can provide ultra-large accessible surface areas and interconnected networks, as well as preventing the undesirable re-stacking phenomena of 2D materials. Herein, we review the synthetic routes and formation mechanism of bulk gel and interface mediated 3D architectures made of diverse 2D materials encompassing both graphene derivatives and non-graphene 2D materials. We also suggest universal strategies that can provide useful insight into application-oriented architecture design. The gelation mechanism is explained in detail; it involves controlled destabilization of the suspension involving a delicate balance between attractive and repulsive interactions. Further, interface mediated self-assembly processes between liquid-solid, liquid-liquid, liquid-gas, and ice-water phases are discussed with a view to tailoring 3D layered and interconnected morphologies. Finally, we highlight the demand for future applications of 2D material-based 3D macroporous architectures. Despite recent progress, more precise control strategies for tuning surface area, pore size distribution, orientation/interconnectivity of pores, density of architectures, and mechanical stability, remain as key scientific and technological barriers that must be addressed to enable practical applications. Further, an important frontier area for future research will involve multilateral hybridization, involving diverse combinations of materials, morphologies, and assembly methods This will provide researchers a multi-dimensional toolbox to access hitherto unavailable properties of 2D material-based 3D architectures for a whole host of applications.